A intuição intelectual em Schelling : da intuição de si mesmo à intuição da natureza - Silva, Kayenne Cristine Vosgeau da (2017)
Our goal is to elucidate the fundamental moments of the instauration of productiveintuition and its disposition as intuition of nature in Schelling. The schellinguian thematization of intellectual intuition in the Philosophical Letters on Dogmatism and Criticism(1975) is presented as the starting point for the insight of nature, and this initial conception seems to result in a dichotomy between dogmatism and criticism. Our research seeks to investigate the passage from the productive intuition to the intuition of nature in the System of Transcendental Idealism(1800). Finally, it is shown how the intuition of nature is definitively established in 1801 in On the True Concept of the Philosophy of Nature and the Correct Method for Solving its Problems(1801). Considering the fundamental moments of the insight of nature, it becomes necessary to acknowledgeas being already present in the Lettersthe fundamental elements that will enable the unity of dogmatism and criticism by instituting the self-intuition of the Subject-Absolute Object itself as a way of access to the Absolute.